2017
DOI: 10.1080/0142159x.2017.1407867
|View full text |Cite
|
Sign up to set email alerts
|

Twelve tips for incorporating and teaching sexual and gender minority health in medical school curricula

Abstract: The World Health Organization has identified many barriers to improving the health of lesbian, gay, bisexual, and transgender (LGBT) patients, including challenges to incorporating and teaching about healthcare for such patients, which we call "sexual and gender minority" (SGM) health content. These challenges include structural and logistical barriers to incorporating SGM health content into undergraduate medical curricula, as well as lack of support in identifying high-quality pedagogical methods for teachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 24 publications
2
30
0
Order By: Relevance
“…Findings from this study support past research that has demonstrated the importance of collaboration in curricular change through stakeholder engagement [42] and the impact of aligning formal and hidden curricula [49][50][51][52]. Collaboration was reported to bolster curricular integration and sustainability of SGM curricula.…”
Section: Discussionsupporting
confidence: 83%
“…Findings from this study support past research that has demonstrated the importance of collaboration in curricular change through stakeholder engagement [42] and the impact of aligning formal and hidden curricula [49][50][51][52]. Collaboration was reported to bolster curricular integration and sustainability of SGM curricula.…”
Section: Discussionsupporting
confidence: 83%
“…Particularly in Japan, incorporating a curriculum on SGM issues in medical schools is crucial to alleviating stigma among healthcare providers. However, even in Western countries, incorporating healthcare for SGM patients into the curriculum is not an easy task, and a variety of efforts have been made to overcome this challenge [22]. At present, only two Japanese medical schools shared outlines of their SGM lectures [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Investigations in the USA, Canada, and South Africa medical schools showed even those students who reported being comfortable about caring for LGBT persons feel unprepared to deal with their specific health issues 54,55 . Solotke et al 56 discussed strategies for incorporating and teaching sexual and gender minority health curricular content in undergraduate education and highlighted that the existence of logistical and structural barriers and difficulties in identifying effective pedagogical methods for teaching sexual and gender minority topics. Based on their real-life experience, the authors provide 12 tips to help educators incorporate sexual and gender minority content in curricula, such as creating a common language around sexual orientation and gender identity; distributing sexual and gender minority health content throughout the curriculum; exploring the complexities of questioning, exploring, and forming a sexual and gender minority identity and their relevance to health; and presenting sexual and gender minority population-specific health content.…”
Section: Genitourinary Sexual Health Ormentioning
confidence: 99%
“…Based on their real-life experience, the authors provide 12 tips to help educators incorporate sexual and gender minority content in curricula, such as creating a common language around sexual orientation and gender identity; distributing sexual and gender minority health content throughout the curriculum; exploring the complexities of questioning, exploring, and forming a sexual and gender minority identity and their relevance to health; and presenting sexual and gender minority population-specific health content. These proposals clarify that approaching LGBT health topics is not an exclusive task of specific disciplines within the curricula (e.g., gynecology in the context of lesbian women) and that students need longitudinal opportunities to develop skills to improve care for the LGBT community 56 .…”
Section: Genitourinary Sexual Health Ormentioning
confidence: 99%